THE EFFECT OF MANGROVE STANDING DENSITY ON CARBON STOCK POTENTIAL IN MARINE COASTAL OF SUNGAITOHOR VILLAGE MERANTI DISTRICT OF ARCHIPELAGO MERANTI RIAU PROVINCE - Muhammad Wahyu Hasibuan; Joko Samiaji; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractMangrove is a tree that normally grows in the intertidal zone of marine coastal environments. The study aim to analyze density of mangrove, to analyze the biomass content, carbon content and ability to absorb carbon dioxide gas in mangrove ecosystem, to analyze the effect of mangrove density on biomass, carbon stock and CO2 uptake and to analyze the comparison of biomass, carbon stock and CO2 uptake between stations. This research was held in November 2017 by survey method and used the data of mangrove species, it’s number and diameter of breast height (DBH) on each sub plot. Measurement of mangrove biomass was done allometric equation method. The result of carbon stock and CO2 uptake in mangrove indicates that Station I was higher than Station II and III.  The result of calculation density of mangrove was equal to 2.839,50 ind/ha. The average yield of mangrove carbon stock and CO2 uptake was 670,89  ton/ha and 2.459,35 ton/ha. As for the average yield of soil organic carbon was 1.758,65 tons/ha. The density of mangrove biomass, carbon content and CO2 uptake which has a strong relationship. The content of biomass, mangrove carbon and CO2 uptake were significantly different (p <0.05) among stations. Keywords: Mangrove, Carbon, Sungaitohor Village